(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2009)
Nada queda atrás is a book of documentary photographs and poetry. The photograghs, shot by Milton Rogovin in 1967, in Quemchi on the island of Chiloé, are today documents which record history and denounce the empoverished conditions in which the fishermen and farmers then lived in Chiloé. The poems, written by Carlos Trujillo, 37 years later in the United Status are, on the one hand, poetic testimonies of the personal and collective memory that the photographs suggest; memories which, in turn, become an imaginary (re)construction of the cultural identity of Chiloé lived by the poet, as a particular experience of foreignity and absence. The poetic texts are, then, derivations of the photographic document, but at the same time they are symbols with which to read/see the photos as metaphors of a profound Chiloé of olden times and today. Seen as such, the book is literally a document of of culture and barbarism: culture as a recognition of the ethics and aesthetics of the “forgotten,” and barbarism as that same recognition reveals stories of postponement and inequality.